Feeding activities of zooplankton in the Bohai Sea - RONG WANG; CHAOLUN LI; KE WANG; WUCHANG ZHANG (Fisheries Oceanography, 1998)
The Bohai Sea was the site of the Chinese national GLOBEC programme. During the June 1997 cruises of R/V Science No.1 , observations and experiments on zooplankton feeding were conducted. At five 48 h time‐series stations the following observations and measurements on zooplankton were carried out: (1) diurnal vertical migration, by collecting samples at different layers every 3 h with a closing net; (2) diurnal feeding rhythms, by gut pigment analysis; and (3) ingestion rate, by both gut pigment analysis and the dilution method. A classification by body size was used to deal with the diversity of species and developmental stages of zooplankton assemblages. Samples were separated into three size groups: small (200–500 μm), medium (500–1000 μm) and large (> 1000 μm). The results showed that the copepods ( Calanus sinicus, Paracalanus parvus, Acartia bifilosa and Centropages mcmurrichi ) performed clear diurnal vertical migrations. However, their behaviour was different at different stations. The variation in gut pigment content over the 24 h cycle showed strong diurnal feeding rhythms, particularly for the large size group. Gut pigment contents reached their daily maximum during the time from dusk to midnight (18:00–24:00). The peak value was about 10 times the minimum observed in the daytime. The in situ daily grazing rate, based on gut pigment contents and evacuation experiments, was 4.00–12.65 ng chl a ind −1 day −1 for the small size group, 5.99–66.58 ng chl a ind −1 day −1 for the medium size group and 31.31–237.13 ng chl a ind −1 day −1 for the large size group. The copepods consumed only a small part (2.90–13.52%) of the phytoplankton biomass but about 77% of the daily production. The grazing mortality rate of phytoplankton by microzooplankton ( −1 The calculated daily consumption of phytoplankton biomass was 35–50%, and 85–319% of the potential production.